Peregrinaciones y viajes de un soldado, después jesuita - Calvo, Thomas (Casa de Velázquez, 2023)
In 1711, in the freezing winter of Madrid, Coadjutor Brother Felipe Frutos, a soldier in the wars of Catalonia in the 1690s, a Jesuit in the convulsive Barcelona of 1701-1705, sat down to write his life, although he had no hope of seeing it published. Why would he take up the quill? For one who had been a small and roguish peasant in the region of Segovia, experiences had accumulated and his prominence had moved from Spain to New Spain, crossing the south of France until he reached Italy. From ship to carriage or on muleback, he had lived unusual adventures in times of misery and cold, a thousand facets that are captured in a writing that is very much his own. Frutos writes as he is: humorous, inventive, self-taught. The study and annotated edition of his diary, which covers the years 1674 to 1711, and of his "Relación sucinta de las propiedades de los indios mexicanos", written in 1722, make this volume an exceptional source to understand the vision "from below" of a universe that extends from Rome to Acapulco, through which some of the most relevant characters and historical events of the period parade, intertwined with the personal perception of Frutos towards Castilians, Catalans, Romans and Indians.